A large prolonged outbreak of hepatitis A associated with consumption of frozen berries, Italy, 2013‐14. Issue 3 (March 2017) - Scavia, Gaia; Alfonsi, Valeria; Taffon, Stefania; Escher, Martina; Bruni, Roberto; De Medici, Dario; Pasquale, Simona Di; Guizzardi, Sarah; Cappelletti, Benedetta; Iannazzo, Stefania; Losio, Nadia Marina; Pavoni, Enrico; et al.
Abstract : Purpose. : In 2013/2014, Italy experienced one of the largest community‐wide prolonged outbreaks of hepatitis A virus (HAV) throughout the country. The article provides a comprehensive description of the outbreak and the investigation carried out by a multidisciplinary National Task Force, in collaboration with regional and local public health authorities. Control strategies of food‐borne HAV infection in both the human and food sectors are also described. Methodology. : Enhanced human epidemiological and microbiological surveillance together with microbiological monitoring of HAV in food and trace‐back investigation were conducted. Results. : A total of 1803 HAV cases were identified from 1 January 2013 to 31 August 2014, in Italy. Sequencing was possible for 368 cases (20.4%), mostly collected between 1 January 2013 and 28 February 2014, and 246 cases (66.8%) harboured an HAV outbreak strain. Imported frozen berries contaminated with HAV were identified as the vehicle of the outbreak which also involved many other European countries in 2013 and 2014. Epidemiological evidence obtained through a case‐control study was supported by the finding of a 100% nucleotide similarity of the VP1/2A sequences of HAVs detected in human and food samples. Trace‐back investigation revealed an extremely complex supplying network with no possibility for a point source potentially explaining the vast contamination of berries found in Italy. Conclusion. : The investigation benefited from an excellent collaboration among different sectors who shared proactively the available information. Our findings highlight the importance of considering frozen berries among the highest risk factors for HAV.